(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2019)
This contribution explores the concept of “sacred space marker” in the Etruscan documentation, applied regardless of the dimensions of the object. It focuses on different scales of representation, from vases to landscape, through the analysis of the ceramic set of the Bocchoris Tomb (Tarquinia) and its contemporary iconographic repertory. Data are presented and analysed in order to sort out consistent indicators that can be used to recognise Tarquinia’s leading figures, responsible for establishing principles and forms of the community space.